Green Bay Packers - Abdo, Kenny, 1986- (2022)
This title focuses on the Green Bay Packers and gives information related to the team's origin in the NFL, their journey through the decades, and highlighting their Hall of Fame players.
Green Bay Packers -- Kick off -- Team recaps -- Hall of Fame.
Includes bibliographical references (page 31) and index.
Ages 7-12
Keywords: Green Bay Packers (Football team) -- Juvenile literature; National Football League -- Juvenile literature